A Study On Security Of Iot: Problems Solving Using Ml And Block Chain (Journal of Pharmaceutical Negative Results, 2023)
As we know IOT is the technology which is most frequently used in number of areas and application since last 10 to 12 years. Using IOT many smart things are communicated via wired and wireless medium and also process, compute and monitor various scenarios in real time. These smart things are different in nature and also having low storage, low power and low processing speed. There are many securities and privacy issues found in traditional system, the existing protocols used in traditional system was not up to mark for IOT. In this review paper, firstly the author explained brief about IOT and its applications. The main security problem ARC (Availability, Reliability and confidentially) and layer -wise problem also identified. After that authors study two main technology ML and block chain for finding privacy issue in Internet of Things.  In the last section of this review paper the security problems are rectified and solved by machine learning and block chain and research challenges also mention.